The Effectiveness of Education and Buerger Allen Exercise on Peripheral Neuropathy Symptoms and Fasting Blood Sugar in Type 2 Diabetes Patients at Hospital X, Bandar Lampung - Simbolon, Alex Candra Martua; Tjitra, Emiliana; Prabawati, Dewi (Pelopor Publikasi Akademika, 2025)
Type 2 diabetes mellitus (DM) is a prevalent metabolic disorder often accompanied by complications such as diabetic peripheral neuropathy (DPN), which impairs sensation and quality of life. Non-pharmacological interventions such as patient education and Buerger Allen Exercise (BAE) have been recommended for managing symptoms and glycemic control, but evidence on their combined effectiveness in clinical settings in Indonesia remains limited. This study evaluated the effectiveness of structured diabetes education combined with Buerger Allen Exercise (BAE) in reducing peripheral neuropathy symptoms and improving fasting blood glucose (FBG) levels among type 2 diabetes mellitus patients. A quasi-experimental one-group pretest-posttest design was employed with 120 purposively sampled patients at Hospital X in Bandar Lampung. The intervention consisted of comprehensive DM education followed by supervised BAE training, performed twice daily for 15 minutes over 14 consecutive days. Neuropathy symptoms were assessed using the Michigan Neuropathy Screening Instrument (MNSI), and FBG was measured with a digital glucometer. Results showed significant reductions in both outcome measures post-intervention (). The mean MNSI score decreased from 5.600 to 2.996, and mean FBG declined from 146.48 mg/dL to 112.59 mg/dL. The proportion of patients with normal FBG increased from 38.3% to 79.2%. Multivariate analysis (MANCOVA) confirmed the intervention's significant effect after controlling for age, gender, and diabetes duration, contributing 44.2% to neuropathy reduction and 18.8% to FBG improvement. The findings demonstrate that integrated education and BAE is an effective, non-pharmacological strategy for managing diabetic complications and glycemic control, suitable for implementation in clinical and self-care settings.